Freedom of Association and the Resurrection of Effective Impossibility? A Comment on Société des casinos du Québec - Hastie, Bethany; Nicol, Keegan (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
In April 2024, the Supreme Court of Canada released its decision in Société des casinos du Québec, which centres on a challenge to the managerial exclusion under Quebec’s Code du travail. This case is the latest in a growing body of Supreme Court decisions that revisit the scope, content, and threshold for claims under section 2(d) of the Charter, which guarantees freedom of association, and works to enlarge the content of section 2(d) as well as its applicability in contexts outside of traditional labour relations regimes.As we discuss in this comment, Société des casinos du Québec risks undoing much of this work—especially for workers who fall outside of those regimes. We argue that this decision may have implicitly resurrected the threshold of effective impossibility for establishing infringement of section 2(d) in non-statutory contexts. In doing so, it has the potential to create a higher threshold for accessing and exercising rights for workers who are not subject to a legislative framework for labour relations, and thus risks creating a tiered approach to accessing associational rights under section 2(d).